207k views
11 votes
Find g(-1) if g(x)=x^3+3x^2+3x+1​

Find g(-1) if g(x)=x^3+3x^2+3x+1​-example-1
User DavidVdd
by
4.9k points

2 Answers

4 votes

Answer:

g-1 =0

Explanation:

x+1 is factor then f(−1)=0

Replace x in p(x) by −1 we get

f(x)=x

3

+3x

2

+3x+1

or,f(−1)=(−1)

3

+3(−1)

2

+3(−1)+1

or,f(−1)=−1+3−3+1

or,f(−1)=0

User Stiv
by
4.1k points
3 votes

Option (c)
0.

Explanation:

Put x = -1 Then,


g( - 1) = {( - 1)}^(3) + 3 {( - 1)}^(2) + 3( - 1) + 1


g( - 1) = - 1 + 3 - 3 + 1

Here, -1 , +1 gets cancelled and +3 , -3 gets cancelled. Hence,


g( - 1) = 0.

User Lindstrom
by
4.7k points